Environmental Laws in Malaysia - an adequate protection of our environment? / Dr. Nor Syamaliah Ngah and Azlina Mohd Hussain - Ngah, Nor Syamaliah; Mohd Hussain, Azlina (UiTM Cawangan Negeri Sembilan, 2022)
As part of a national management system, sound environmental laws and policies are essential for the long-term development of any given country. Malaysia is a member of the ASEAN Declaration on Environmental Sustainability, which pledges to "support the conservation and sustainable management of essential ecosystems, including forests, coastal and marine habitats, and to raise the ASEAN region’s cumulative forest cover". Malaysia has undergone a tremendous structural shift, going from an agriculture-based economy to a manufacturing-based economy, with considerable social changes, in tandem with its extraordinary economic growth over the last two decades. Despite this rapid development, the natural ecosystem has suffered serious consequences.